Applying the phenotype approach for rosacea to practice and research. (17th September 2018) - Tan, J.; Berg, M.; Gallo, R.L.; Del Rosso, J.Q.
Summary: This thoughtful article has been presented by a group of authors from departments in Canada, Sweden and the USA. The central point of this article is the case for a different approach to the classification of the skin disease, rosacea, although the argument is also relevant to other diseases. Currently rosacea is divided into a number of different subtypes based on presence or absence of flushing or transient redness of the face, swelling of the nose, small spots (without or without heads) and broken veins or telangiectases. The authors are arguing for a less restricted approach which uses a combination of different terms, some of which are regarded as major and others as minor, that together best describe the changes on the skin that each patient shows to account for the fact that patients may have several such changes at the same time or one may evolve into another. It also allows greater flexibility. Adopting this "phenotype" approach, and thereby taking into account all the features of the condition, would allow better assessment of the effects of treatment on each patient, in clinical trials, or in understanding the disease, or the impact of rosacea on a patient's life. How we describe things in medicine often limits our ability to understand disease and its treatment and impact. This paper argues for greater flexibility in using what we see to classify illness. Abstract : Linked Article: Tan et al. Br J Dermatol 2018;179 :741–746